Monument to Fernand Deligny - Bonfim, Gabriel; Frizzo, Guilherme Bruschi (Farol, 2025)
The present text is an exercise in performance writing that traces in its course an account of the failure of two art teachers from the municipal education network of Florianópolis (SC). It is triggered by the writing of Fernand Deligny, memorable for his work in educational centers and for his critique of their imprisonment character. The educator, who accompanied marginalized youth for more than fifty years, thought of education as a way of finding possible ways of living in excluding contexts. Writing with him means making visible the role of writing and reading in critical educational action, as devices of support and care. With Deligny, failure becomes dance.
Keywords: failure; art education; institutional critique; performative writing